PENGUJIAN MODEL TQM EUROPEAN QUALITY AWARD (EQA) UNTUK BEBERAPA PERUSAHAAN DI INDONESIA - Masduki, M (Jurnal Teknik Industri, 2003)
Rate of business competitive and customer voices changing give a stress to an organization to produce a high product quality and also a good management. Award model of quality management is a system model of quality that's used to measure reaching and testing, A fit management model of quality to be usedt o businesse nvironmenti n Indonesia.T his researchw as done using steps, whose are deep analysis and sistematic on award totally quality management which is implemented in progressed country (Deming price, Malcolm Baldrige, and European Foundationf or Quality Management) D, eveloping of totally quality management model and measwing to conn?ction among the empirie model of data that have got by sample in a company and also give recommendation of implementing total quality management based on developed model. The result of this research is hoped to answer a question connecting with work planning of implementing total quality management of organization in Indonesia.